Simulation 1x2 Microstrip Antenna Array with Truncated Corner and Partial Ground Modification at 2.4 GHz for WiFi Applications - Amillia, Fitri; Yadi, Sukri (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
WiFi performance is highly dependent on the quality of the antenna as a system for transmitting and receiving electromagnetic signals. A 1×2 microstrip array antenna for 2.4 GHz WiFi applications with truncated corner and partial ground techniques has been successfully designed and simulated. The adjustment of the truncated corner strategy is to cut the four corners in a rectangular shape on the fix side and the fractional ground strategy on the ground plane. The recreation was carried out utilizing CST program. The results showed an increase in antenna performance in terms of return loss, bandwidth, and gain. The designed antenna showed a return loss of -28.57 dB, a bandwidth of 657MHz, and a gain of 6.05 dBi.These results indicate that the combination of array and structural modifications can significantly improve the performance of microstrip antennas for WiFi applications.